PROMOTING AND MAINSTREAMING SUSTAINABILITY PRACTICES IN AGRI-FOOD SUPPLY CHAINS - Maria KONTOPANOU; Giannis T. TSOULFAS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Sustainability consists one of the biggest challenges that the agri-food supply chains have to face. Examining agrifood supply chains from a “life-cycle” perspective has been promoted as an effective way to move towards more sustainable food production systems. The adoption of such viewpoints in the agri-food sector has a great impact on the environmental, the economic, the social and the institutional dimensions of agri-food supply chains. Relevant technical and managerial solutions have been gaining increasing relevance in the agricultural activities, and stakeholders have a variety of alternative solutions at their disposal to increase the efficiency of the agri-food supply chains. This review examines and categorizes the strategies that have been followed towards promoting sustainability in agri-food supply chains 'from farm to fork’. Moreover, our aim is to shape an analytical framework to accommodate decisions concerning supply chain design and operation towards sustainability.